The perspectives of university students on gender roles Üniversite öğrencilerinin toplumsal cinsiyet rollerine ilişkin bakış açıları - Dinç, Ayten; Çalışkan, Cüneyt (Journal of Human Sciences, 2016)
Objective: This study was performed as a descriptive study in order to determine the perspectives of university students on gender roles. Method: The population of the study was composed of the students who currently study in the department of Emergency and Disaster at the School of Health in Çanakkale Onsekiz Mart University. The study was performed with a total of 224 students present at the school on the date when the study was carried out and agreed to participate in the study. The study was conducted between 27 March-28 May 2014.A survey form prepared in accordance with the literature and Gender Roles Attitude Scale (GRAS) were utilized in the study so as to gather the data. The data were evaluated by means of descriptive statistics, t-test, Mann-Whitney U and variance (one-way ANOVA) test. Findings: Among the students who participated in the study, 49.6% of them were male whereas 50.4% were female. In the study, the average of the total scores on the GRAS of the female students was 155,17±16,47 while that of the male students was 129,56±20,52. In regard to the analysis of the sub-dimensions of the GRAS by gender, it was determined that the female students hold more “egalitarian attitudes” on gender roles than the male students do. With respect to the effect of socio-demographic characteristics of the students on their attitudes towards gender roles, it was found out that there was no difference among the students in terms of age, grades, the high school that the students graduated from, place of residence, the presence or absence of working parents, economical levels, number of sisters/brothers, educational status of the parents. However, in regard to the type of family, it was found that the students with an elementary family hold more egalitarian attitudes. Result: The study concluded that the perspectives of the female students and those of the male students are different from each other. These results have revealed that the universities with the objective to raise intellectual individuals should enable their students to gain awareness on gender roles as well as acquire the fundamental vocational information. Özet Amaç: Bu çalışma üniversite öğrencilerinin toplumsal cinsiyet rollerine ilişkin bakış açılarını belirlemek amacıyla tanımlayıcı olarak yapılmıştır. Yöntem: Araştırmanın evrenini Çanakkale Onsekiz Mart Üniversitesi Sağlık Yüksekokulu Acil Yardım ve Afet Yönetimi Bölümüne devam eden öğrenciler oluşturmuştur. Araştırmanın yapıldığı tarihte okulda bulunan ve araştırmaya katılmayı kabul eden 224 öğrenci çalışma kapsamına alınmıştır. Araştırmanın uygulaması 27 Mart-27 Mayıs 2014 tarihleri arasında yapılmıştır. Çalışmada, veri toplamak amacıyla literatür doğrultusunda hazırlanan anket formu ve Toplumsal Cinsiyet Rolleri Tutum Ölçeği (TCRTÖ) kullanılmıştır. Verilerin değerlendirilmesinde tanımlayıcı istatistikler, t-testi, mann-whitney U ve varyans (one-way anova) testleri kullanılmıştır. Bulgular: Çalışmaya katılan öğrencilerin %49.6’sı erkek, %50.4’ü kız öğrencilerden oluşmaktadır. Araştırmada öğrencilerin TCRTÖ toplam puan ortalamasının kızlarda 155,17±16,47, erkeklerde 129,56±20,52 olduğu belirlenmiştir. Cinsiyete göre TCRTÖ alt boyutları incelendiğinde; kız öğrencilerin erkek öğrencilerden daha fazla, toplumsal cinsiyet rollerine ilişkin ‘eşitlikçi tutuma sahip’ olduğu saptanmıştır. Araştırmada öğrencilerin sosyo-demografik özelliklerinin, toplumsal cinsiyet rollerine ilişkin tutumları üzerindeki etkisine bakıldığında ise, yaş grupları, sınıflar arası, bitirilen lise, yaşadıkları yer, anne babanın çalışma durumu, ekonomik düzeyleri, kardeş sayıları, anne babanın eğitim durumu açısından aralarında fark olmadığı belirlenmiştir. Ancak aile tipi açısından çekirdek aileden gelen öğrencilerin daha eşitlikçi bir yaklaşım sergiledikleri saptanmıştır. Sonuç: Araştırmada kız ve erkek öğrencilerin toplumsal cinsiyet rollerine ilişkin görüşleri arasında fark olduğu saptanmıştır. Bu sonuçlar aydın bireyler yetiştirmeyi hedefleyen üniversitelerde öğrencilere temel mesleki bilginin yanı sıra toplumsal cinsiyet eşitliği konusunda duyarlılık kazandırılması gereğini göstermektedir.